Comparison of hematological and histological analysis of "Clinomon" and "Litovit-M" in mice - Oyuntsetseg, J; Odnoo, P; Ganbaatar, J; Mandakhsaikhan, L; Tsogtsandan, L (Mongolian Journal of Chemistry, 2014)
DOI: http://dx.doi.org/10.5564/mjc.v13i0.157 Mongolian Journal of Chemistry Vol.13 2012: 31-36